Proceedings of the International Conference on English Language Teaching (ICONELT 2019) 2020
DOI: 10.2991/assehr.k.200427.033
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitudes Towards the Use of Google Forms as an Online Grammar Assessment Tool

Abstract: The use of online assessment tool has been a debatable issue among teachers. However, it can be easy for teachers to assess students' understanding. They could use an online assessment tool such as google form to examine grammar understanding. This study was aimed to find out students' attitudes of junior high school students using google forms in their assessment. This research used a qualitative design to take the data. This research was conducted at MTs Masyhudiyah Gresik with 25 students as the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Google form is a web-based that can be shared to the other people by sending a link or emailing a message and can be used for variety of productivity task and create various types of questions, such as drop down menus, multiple choice, check list, rating scale, short answers text boxes and etc. (Adelia et al, 2021;Jazil et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Google form is a web-based that can be shared to the other people by sending a link or emailing a message and can be used for variety of productivity task and create various types of questions, such as drop down menus, multiple choice, check list, rating scale, short answers text boxes and etc. (Adelia et al, 2021;Jazil et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies on students' perceptions of Google tools in English learning online have been identified, which were conducted either with separate Google applications such as Google Classroom [35], [37], [42]; Google Forms [43], [44]; Google Meet [45]; Google Sites [46], [47]; Google Docs [48], [49], and Google Translate [5], [50],…”
Section: Previous Studies On Students' Perceptions Of Google Tools In...mentioning
confidence: 99%
“…Some scholars have highlighted the advantages of some online formative assessment tools, namely Google Forms, Blackboard, Plickers, Socrative, and Kahoot! (Alharbi and Meccawy, 2020;Dobson, 2008;Elbasyouny, 2021;Fageeh, 2015;Jazil, Manggiasih, Firdaus, Chayani, & Rahmatika, 2020). These platforms are perceived as positive tools that enhance students' achievement in different ways.…”
Section: Perceived Usefulnessmentioning
confidence: 99%